Professional learning and the on-line discussion - Michael Hammond (Information Research: An International Electronic Journal)
This paper explores the growing interest in professional development through asynchronous electronic discussion. It presents an excerpt from within a recent forum on telematic learning and analyses ways of initiating discussion; styles of messages and learning through on line discussion. The paper suggests that electronic forums have huge potential for developing professional knowledge but points out some of the complexities and paradoxes involved.